Hafnium dioxide (HfO2) as micro-crucible liner on GeOI for Rapid Melt Growth (RMG) structure - Zainal, N.; Mitchell, S. J. N.; McNeill, D. W. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presented an evaluation of hafnium dioxide (HfO2) used as insulator and micro-crucible in the modification of rapid melt growth (RMG) structure. A 20 nm HfO2 have been deposited on silicon (Si) and silicon on insulator (SOI) substrates using Atomic Layer Deposition (ALD). Samples encapsulated with HfO2 in the RMG structure shows free from cracks and delamination even heated at higher annealing temperature (1049 oC) that observed by Scanning Electron microscopy (SEM), Transmission Electron Microscopy (TEM) and Focus Ion Beam (FIB). The quality of germanium (Ge) thin-film is characterised using micro-Raman Spectroscopy. Results show that samples with HfO2 microcrucible liner on Si substrate gives the Ge-Ge peak position lies at 299 cm-1, indicating that the 20 nm HfO2 layer gives slightly tensile strain with a small shift in peak position compared to the bulk reference value of 300.2 cm-1. The Raman peak position for samples on SOI substrate increased approximately 0.3 cm-1 to 299.3 cm-1 indicating lower stress. The Raman peak of this sample had an increased Full width at half maximum (FWHM) of 3.9 cm-1 which is believed to be mainly due to the presence of HfO2 and scattering of Raman laser.